An obesity strategy to reduce COVID-19 morbidity and mortality. (27th May 2021) - Glasper, Alan
Abstract : Emeritus Professor Alan Glasper, from the University of Southampton, discusses the recently launched campaign in England with a package of measures to help people lose weight and mitigate effects of COVID-19